Electronic customer relationship management (E-CRM), customer experience and customer satisfaction: evidence from the banking industry. Issue 2 (27th May 2021) - Kumar, Pushpender; Mokha, Anupreet Kaur; Pattnaik, Subash Chandra
Abstract : Purpose: The purpose of this paper was to examine the relationship between electronic customer relationship management (E-CRM) and customer satisfaction through the mediating role of customer experience in the banking industry. Design/methodology/approach: The data were collected from customers of 10 banks (5 public and 5 private sector banks) of Delhi, India. In total, 836 useable structured questionnaires were filled, and the data were analyzed using structural equation modeling (SEM) through AMOS. Findings: The results revealed that customer experience mediated the relationship between E-CRM and customer satisfaction confirming well with the hypothesized model. Research limitations/implications: The model was tested in the domain of banking industry; future results may be conducted in different domains for improving generalizability. A comparative study between public and private sector banks in terms of E-CRM, customer experience and customer satisfaction could also be conducted. Originality/value: The study was the first to unequivocally analyze the influence of the E-CRM on customer satisfaction through customer experience in the banking industry. The study also introduced stimulus-organism-response (S-O-R) model as a theoretical support to associate E-CRM to customer satisfaction through customer experience. Thus, this study will enhance the current knowledge base and will also aid E-CRM managers amid decision-making process.